2022
DOI: 10.1111/echo.15299
|View full text |Cite
|
Sign up to set email alerts
|

Definition, prevalence, and clinical significance of mitral annular disjunction in different patient cohorts: A systematic review

Abstract: Background: Mitral annular disjunction (MAD) is a structural abnormality involving a distinct separation of the left atrium/mitral valve annulus and myocardium continuum.The literature around MAD has increased over recent years, thus we sought to review the current data on the definition, prevalence, and clinical outcomes of MAD.Methods: A search of MEDLINE and EMBASE was conducted to identify studies which evaluated MAD in any patient cohort. The study results were synthesized narratively.Results: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…In line with the current literature, this case features a young female with numerous factors that are characteristic of MAD 3–5 . Together with a MAD distance of 8.5 mm by TTE, the associated factors include palpitations, 2 syncope, 3 low ejection fraction (51 ± 5%), 2 chest pain and ventricular arrythmia 6 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In line with the current literature, this case features a young female with numerous factors that are characteristic of MAD 3–5 . Together with a MAD distance of 8.5 mm by TTE, the associated factors include palpitations, 2 syncope, 3 low ejection fraction (51 ± 5%), 2 chest pain and ventricular arrythmia 6 .…”
Section: Discussionsupporting
confidence: 79%
“…Importantly, what is clear is that ventricular arrhythmia is associated with MAD, independent of concomitant MVP 2 . With MAD, ventricular arrhythmias and SCD are the most immediate concern, as 10%–12% will experience a life‐threatening cardiac arrhythmic episode in their lifetime 2–4 . In our case, the Holter monitor recorded for a period of 26 h and 47 min, during which time there was no supraventricular ectopy.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In total, available studies suggest that the prevalence of MAD is between 16% and 55% in patients with MVP and/or severe MR. 7,13–16 A recent systematic review of12 studies reported a pooled prevalence of MAD of 30.1% for patients with MVP and/or Barlow’s disease and 8.7% for the general population. 17…”
Section: Prevalencementioning
confidence: 99%
“…Mitral annular disjunction (MAD) has a strong association with ventricular arrhythmias and sudden cardiac death [ 40 ], with a prevalence of 30.1% in MVP patients [ 41 ], and is independently associated with excess risk for arrhythmic events [ 42 ]. Previous studies have suggested that MVP strongly predicts MAD [ 43 ].…”
Section: Discussionmentioning
confidence: 99%